Religious Education Based on Local Wisdom “Satu Tungku Tiga Batu” in Fakfak Community West Papua - Indria Nur (UIN Sunan Ampel Surabaya, 2022)
This article examines one of the strategic efforts to prevent the spread of ideology of radicalism and terrorism, even conflict through religious education based on local cultural values as an effort to instill tolerant citizenship attitudes and uphold religious, national and state identities so that they remain inherent among the younger generation. Based on the result of the phenomenological qualitative research as well as interview data and observation on the indigenous peoples of Fakfak regency of west Papua, the local wisdom of “Satu Tungku Tiga Batu” in the multi etnic and multi religious Fakfak indigenous communities is able to internalize its cultural values into cohesive and reflecting values in the character of its strong citizens. Local wisdom “Satu Tungku Tiga Batu” in addition to functioning to maintain harmony and brotherhood, the concept of a three stone furnace also functions as a fakfak community identity that has a tolerant attitude, prioritizes the public interest rather than personal interest, honestly, does not like to interfere in the affairs of others and love one another. Local wisdom based religious education is presented not only in school educational, but also in family and community settings. This is evident from the existence of the people of Fakfak of west Papua who are very tolerant of one another, so that harmony in religious and social life is maintained, even interethnic and interfaith conflicts can be said to never occur.